Using participatory action research to co-design perinatal support strategies for Aboriginal and Torres Strait Islander parents experiencing complex trauma. Issue 5 (September 2022) - Reid, Carol; Gee, Graham; Bennetts, Shannon K.; Clark, Yvonne; Atkinson, Caroline; Dyall, Danielle; Nicholson, Jan M.; Chamberlain, Catherine
Abstract: Problem & background: Support is important for all parents but critical for those experiencing complex trauma. The The Healing the Past by Nurturing the Future project uses participatory action research to co-design effective perinatal support for Aboriginal and Torres Strait Islander parents. Aim: This research aims to identify and refine culturally appropriate support strategies for Aboriginal and Torres Strait Islander parents experiencing complex trauma. Design: We presented our synthesised eight parent support goals and 60 strategies, collated from Elder and parent focus groups, previous participatory workshops, and evidence reviews, for discussion at a stakeholder workshop. Stakeholder perspectives were captured using a three-point agreement activity and, self- and scribe-recorded comments. Aboriginal and non-Aboriginal researchers analysised the qualitative data, to identify core factors which might facilitate or help enact the parenting related goals. Findings: Overall, stakeholders (n = 37) strongly endorsed all eight goals. Workshop attendees (57% Aboriginal) represented multiple stakeholder roles including Elder, parent and service provider. Four core factors were identified as crucial for supporting parents to heal from complex trauma: Culture (cultural traditions, practices and strengths), Relationality (family, individual, community and services), Safety (frameworks, choice and control) and Timing (the right time socio-emotionally and stage of parenting). Discussion: Context-specific support tailored to the Culture, Relationality, Safety, and Timing needs of parents is essential. These four factors are important elements to help enact or facilitate parenting support strategies. Conclusion: Further work is now required to develop practical resources for parents, and to implement and evaluate these strategies in perinatal care to address cumulative and compounding cycles of intergenerational trauma.